Surface electromyography to identify top-down modulation in complete chronic spinal cord injury - SIMÃO, Camila R.; DE HOLANDA, Ledycnarf J.; URBINI, Lilian F.; LACERDA, Matheus O.; FERNANDES, Karina; DA SILVA, Patrícia M.; MORYA, Edgard; LINDQUIST, Ana R. (European journal of physical and rehabilitation medicine, 2022)
Complete spinal cord injury (SCI) is characterized by permanent loss of nerve impulse propagation through the injury level leading to complete loss of voluntary muscle contraction. However, clinically undetectable top-down modulation of lower limbs might be present and can be evidenced using surface electromyography (sEMG). A subject with complete chronic SCI and no spasticity presents voluntary modulation of sEMG signal during a task-specific activity associated with sensory input. We present for the first time the spectral characterization of sEMG signal in response to orthostatic training associated with voluntary movement attempts in complete SCI. Behavior of sEMG signal varied according to kinematic properties of movement, reinforcing the voluntary influence of efferent pathways on motor output. Our findings will contribute to elaborate evaluation protocols to investigate the preservation of corticospinal activities, and to evolve more accessible strategies in a clinical setting.